On comparison of the estimators of the Hurst index and the diffusion coefficient of the fractional Gompertz diffusion process - Kubilius, Kęstutis; Melichov, Dmitrij (Nonlinear Analysis: Modelling and Control, 2016)
We study some estimators of the Hurst index and the diffusion coefficient of the fractional Gompertz diffusion process and prove that they are strongly consistent and most of them are asymptotically normal. Moreover, we compare the asymptotic behavior of these estimators with the aid of computer simulations.